Relationship of Cigarette Smoking and Time of Quitting with Incident Dementia and Cognitive Decline - Deal, Jennifer A. (J Am Geriatr Soc, 2019)
IMPORTANCE: Understanding how dementia risk is impacted by timing of smoking cessation has public health implications for prevention efforts. OBJECTIVE: Investigate the relationship of cigarette smoking and cessation with dementia risk and cognitive decline in the Atherosclerosis Risk in Communities (ARIC) Study. DESIGN AND SETTING: Begun in 1987–1989, ARIC is an ongoing prospective cohort study conducted in 4 US communities. PARTICIPANTS: 13002 men and women (25% African American) aged 52–75 years. MAIN OUTCOME AND MEASURES: All-cause dementia was defined using standardized algorithms incorporating longitudinal cognitive data, proxy report and hospital and death certificate dementia codes. Cognitive decline was measured using a composite cognitive score created from 3 tests measured at 2 time points (1996–1998 and 2011–2013). Smoking and cessation status were defined by self-report using data from 1987–1989 (visit 1) and 1996–1998 (visit 4). Incident dementia risk and differences in cognitive change by smoking status were estimated with Cox proportional hazards and linear regression models, respectively. To address smoking-related attrition, cognitive scores were imputed for living participants with incomplete cognitive testing. RESULTS: The proportion of never, former and current smokers was 44%, 41% and 14%; 79% of former smokers quit ≥ 9 years prior to baseline. A total of 1347 participants developed dementia. After adjustment, compared to never smoking, the hazard ratio for all-cause dementia for current smoking was 1.33 (95% CI: 1.12, 1.59), and for recent quitting (<9 years prior to baseline) was 1.24 (95% CI: 1.01, 1.52). Quitting ≥ 9 years prior to baseline was not associated with dementia. We found no differences in rates of cognitive decline by smoking status. CONCLUSIONS AND RELEVANCE: Although quitting at any time suggested benefit, dementia risk depended on time since smoking cessation. Our study highlights the importance of early midlife cessation to decrease dementia risk.